Letter - Lane, John
1941-03-12 013-0048-001 Dartford Trades Council and Labour Party. INDUSTRIAL SECTION. Chairman : Secretary: John Lane OFFICES : 205 Station Rd Dartford Heath Dartford Kent 12/3/41 Sir W. Citrine Gen. Sec. T.U.C. Dear Sir and Bro, The above body heard, with very deep regret, of the murder of Senor Companys, by the Franco government. International report has it that the same fate is being prepared for the one-time Spanish President and Trade Union leader, Largo Cabballero. There is not the slightest doubt that Senor Caballero can be saved if the British Trade Union movement so desires. We appreciate, of course, that the strange "Bed-fellows" we find ourselves with these days, might be embarrased by an agitation in defence of an international working-class leader. But it seems to us that the feelings of that great appeaser, Sir Samuel Hoare, are worth but small consideration against our duty to Caballero. On behalf of the Trades Council yours fraternally John Lane. 292/946/13/48(i)